FACTORS THAT ASSOCIATED WITH REPRODUCTIVE HEALTH KNOWLEDGE AMONG ADOLESCENTS DURING COVID-19 PANDEMIC IN DKI JAKARTA. - Oktafiyanti, Arnur; Pristya, Terry Y. R.; Herbawani, Chahya K.; Hardy, Fathinah R. (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTBackground: Covid-19 was bring many effects to adolescent group. According to the data of the report of the visit of Youth Care Health Service (YCHS) in DKI Jakarta in 2020 reflect that the reproductive health condition of adolescents is still bad during the Covid-19 pandemic. Adolescent's lack of knowledge about reproductive health is one of the main predictors of existing reproductive health problems. Purpose: This study aimed to determine the strongest factors associated with reproductive health knowledge among adolescents in DKI Jakarta during the Covid-19 pandemic. Methods: The study used a quantitative method with online based study and a cross-sectional as a design study. Respondents were calculated with Accidental Sampling and obtained 400 respondents. The chi square test and multiple logistic regression test was undertaken to analyze data with α = 0,05. Results: The results of univariat test obtained 87,3% respondents have good reproductive health knowledge. Chi Square test obtained that the significant value of the reproductive health knowledge with gander, education level, media information, and peer influence. Based on Multiple Logistic Regression test, adolescents male had a 5,629 probability to having less knowledge of reproductive health (95% CI 2,95-11,757) compared to aldolescents girls after being controlled by the level of education and peer influence. Conclusion: There was a correlation between reproductive health knowledge with gender, education level, and peer influence among adolescents during Covid-19 pandemic in DKI Jakarta. ABSTRAK Latar Belakang: Pandemi Covid-19 membawa dampak bagi remaja. Berdasarkan laporan kunjungan Pelayanan Kesehatan Peduli Remaja (PKPR) wilayah DKI Jakarta tahun 2020 disebutkan bahwa kondisi kesehatan reproduksi remaja masih menghawatirkan selama masa pandemi Covid-19. Kurangnya pengetahuan remaja tentang kesehatan reproduksi menjadi salah satu prediktor utama masalah kesehatan reproduksi yang ada. Tujuan: Tujuan penelitian untuk mengetahui faktor yang berhubungan dengan pengetahuan remaja tentang kesehatan reproduksi pada masa pandemi Covid-19 di DKI Jakarta. Metode: Penelitian menggunakan metode analitik berbasis online dengan desain study cross-sectional. Pengumpulan data menggunakan accidental sampling dan diperoleh 400 responden. Analisis data menggunakan uji chi square dan regresi logistik berganda dengan α = 0,05. Hasil: Hasil analisis univariat menggambarkan sebagian besar remaja memiliki pengetahuan kesehatan reproduksi yang baik (87,3%). Hasil uji Chi Square diperoleh ada hubungan antara jenis kelamin, tingkat pendidikan, media informasi, dan pengaruh teman sebaya terhadap pengetahuan kesehatan reproduksi. Berdasarkan hasil uji Regresi Logistik Berganda menunjukkan remaja laki-laki berpeluang 5,629 kali (95%CI: 2,95-11,751) untuk memiliki pengetahuan yang kurang tentang kesehatan reproduksi dibandingkan dengan remaja perempuan setelah dikontrol oleh tingkat pendidikan dan pengaruh teman sebaya. Kesimpulan: Terdapat hubungan antara pengetahuan kesehatan reproduksi dengan jenis kelamin, tingkat pendiidkan dan pengaruh teman sebaya pada remaja selaa pandemic Covid-19 di DKI Jakarta